Gambaran Konflik pada Keluarga dengan Lansia - Ansar, Wilda; Wahyuni, Sri; Putri, Nur Mazaya; Supiyanti, Nur Anindi (SOCIETIES: Journal of Social Sciences and Humanities, 2024)
Abstract. Family conflicts with the elderly are a significant issue that requires attention. This research aims to provide a picture of the conflicts that commonly occur in families with the elderly. A search for relevant articles was conducted using the keywords: "Family conflicts with the elderly," "Causes of family conflicts with the elderly," and "Strategies for resolving family conflicts with the elderly." A total of 20 journals were obtained from Google Scholar and reviewed systematically using the Metasynthesis Qualitative Research method. The findings revealed that the causes of conflicts can be categorized into three main factors: fatigue in caring for the elderly, generational gaps between the elderly and their families, and differences in perceptions of care and needs between the elderly and their families. Additionally, two strategies were suggested for resolving family conflicts with the elderly: providing care training to families and using coping strategies by families. The results of this research are expected to serve as a basis for policy-making and intervention to improve the well-being of families with the elderly.Keywords: Family, Elderly, Conflict